Fortifikasi Cita Rasa Cake Melalui Penambahan Tepung Sukun Hasil Fermentasi - Hartati, Hartati; Rachmawaty, Rachmawaty (bionature, 2017)
Abstract. One of the bread tree utilization is to make it powder. In general, the bread tree powder has good taste and good condition than tapioca powder. so, it can produce many kinds of delicious product. Several kinds of food that can make from the bread tree powder are cake, pastry, donuts, pudding, kroket, rissoles, gethuk, klepon, apem ect. The aim of this research is to know the acceptance number (organoleptic) of cake that made from the bread tree powder from fermentation process if we compare with the cake from wheat flour. This research consists of 3 treatments; A1 (cake from wheat flour), A2 (cake from the bread tree powder) and A3 (cake from the bread tree from fermentation process). The product was tested by organoleptic test (taste, smell and texture). Based on the research we know that the taste of A3 product is the most like (62 %) then A1 (48%) and A2 (33 %). The smell of A3 product is the most like (48%) then A1 and A2 (like and dislike just 38%), and the best texture is A1 (67%), A2(48%).Keywords:fortification, cake, fermented the bread tree powderÂ Â